The Theology and Culture of Marriage in Nigerian Evangelical Film - Olayiwola, Elizabeth (Evangelical review of theology, 2020)
Nigerian evangelicals have embraced filmmaking as a way to share Christian truth, but their transnational films expose the significant worldview differences between Christian cultures in Nigeria and the West. This article probes the somewhat mixed messages that appear in videos by Nigeria's best-known evangelical film producer, Mike Bamiloye.